Pelayanan Kesehatan Tradisonal pada Panca Indra - Liss Dyah Dewi Arini; Bernadytha Ratriani Putri; Dwi Setia Ningsih; Nayla Az-zahra Wahyudi; Sekar Citra Prasetya (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Traditional wellness,which is an integral part of every society’s cultural heritage,offers a holistic approach to maintaining balance in the boddy,mind and spirit.This article reviews various traditional practices such as herbal medicine,acupunture,and yoga that have become and intergral part of the health care sistem in many countries.Through and understanding of energi balance,the use of medicinal plants and healing techniquesthat have beein passet down trough generations,people maintain their health while preserving the richness of their culture.The importance of maintaining sustaina bility and recoknizing traditinal health prachtices in a modern context is also discussed.By integrating traditional knowledge with contemporary medical practices,we can optimize the overall health and well-being of sociaty.